Leadership in Islam Thoughts, Processes and Solutions in Australian Organizations - Faris, Nezar (Springer International Publishing, 2018)
This book examines the concept of leadership from within the Islamic worldview, exploring its meaning and various manifestations through textual evidence from the two primary sources of Islam, The Qur'an and hadith. Using this theoretical framework concurrent with contemporary leadership theory, the authors scrutinise the distinctive leadership dynamics of Islamic organisations within a minority-Muslim context and a focus on Australia. Drawing on empirical data gathered over four years, the nature of leadership and its processes within this unique context is examined. Leadership in Islam reconciles the problematic processes that exist within Muslim organisational context and offers a set of measures and strategies to improve leadership processes including enacting leadership, enacting following, accommodating complexity, sense making and embracing basics as the core processes. This book will be beneficial for anyone who seeks to understand the meaning of leadership in Islam, the way Islamic organisations operate, and the way forward for improving leadership processes within an Australian/Western context.